Produção de identidade e modos de objetivação/subjetivação do sujeito tatuado na revista Inked - Godoi, Edileide de Souza (2015)
It being understood that the subjects inserted in a society of speeches increasingly ephemeral, submissive liquidity of postmodernity, find in the practice of tattooing a return place to yourself,the general objective of this thesis is to analyze how the tattooed subject is constituted and how he is produced in the Inked Magazine in the period from 2010 to 2012. This problematic isanchored on the following question: why the subjects inserted in a society of speeches, which dissolve faster than the time it takes to mold them, mark their bodies with tattoos that will accompany them for a lifetime? Do these subjects, at all the moment disciplined, standardized by social control mechanisms, areable by self to subjective the practice of tattooing? To answering such questions, It analyzes a corpus of utterances with syncretic materiality (verb-visual) in nine covers of Inked and in some sections of the magazine, linking them to other materiality that enter, interdiscursively, inside the archive in purpose to discuss how the games of truth are produced that, subtly, teach and propose the subject ways of behaving. Methodologically, this research is characterized as documentary and bibliographic, of descriptive and interpretative character. It subsidizes the analyses on the theoretical reference of Discourse Analysis, in particular that support in arch genealogical Foucault study around the constitution of the subject, who are affected by the relations of power-knowledge. Moreover, it is guided in the contributions of the fields of Historical Semiology, with Jean-Jacques Courtine, as well as at the field of Sociology, especially with Zygmunt Bauman ideas and still it refers to the field of Cultural Studies to discuss the issue of identity in a socio-cultural and discursive perspective and the practice of tattooing in the media. This media acting as an institution that fixes, keeps and give a new meaning to the identities. The results show that the modes of objectification/ subjectivation of tattooed in the magazine that is on the agenda are produced for several tecnology of the self and that them are crossed by official discourses and ratified by the discursive practices of biotechnologies directed to the body. This discoursivity, without repressive connotation, opens each more time space for pratices of freedom and self-goverment in processes of subjectivation of the tattooed at contemporanity.